A framework for describing block cipher cryptanalysis - Phan, Raphael C. W.; Siddiqi, Mohammad Umar (IEEE Computer Society, 2006)
Block ciphers provide confidentiality by encrypting confidential messages into unintelligible form, which are irreversible without knowledge of the secret key used. During the design of a block cipher, its security against cryptanalysis must be considered. History has shown that a cipher designed without an adequate treatment of this will often lead to flaws and attacks by other researchers, sometimes devastatingly so. The problem for an aspiring cipher designer is that there are no standard texts on block cipher cryptanalysis because it is a fast changing field. The commonly available references are academic journals and conference proceedings, which may not be easy to grasp for researchers new to cryptanalysis. This paper presents the Xi framework, which is designed to compactly describe the block cipher cryptanalysis techniques regardless of their individual differences. This provides the cryptanalyst with a general framework to describe attacks on block ciphers, with the additional capabilities of allowing specification of the technical details of each different type of attack and of comparison of their respective strengths. Comparing different distinguishers in this framework also allows us to see natural generalizations and trigger nice open problems. We then show how to apply this Xi framework to the description of various attacks on popular and recent block ciphers.